TNM atlas - Wittekind, Ch. (Christian); Asamura, H.; Sobin, L. H. (Hoboken, NJ ; Chichester, West Sussex, UK : Wiley-Blackwell, 2014)
This book presents the illustrated version of the TNM Classification of Malignant Tumours, Seventh Edition, promoting the uniform application of the TNM classification in cancer practice. Now featuring beautiful, useful full-color medical artwork, this book is designed as an aid for the practical application of the TNM classification system by illustrating the T and N categories in clear, easily understood graphics. The aim of this presentation is twofold: to reach a more standardized understanding and documentation of the anatomic spread of tumours, and to further enhance the dissem.
Kidney (ICD-O C64) (Fig. 450)Renal Pelvis and Ureter(ICD-O C65, C66); Urinary Bladder (ICD-O C67); Urethra; Adrenal Cortex Tumours (ICD-o C74.0); Hodgkin Lymphoma; Non-Hodgkin Lymphomas.
Print version record and CIP data provided by publisher.
Keywords: Tumors -- Classification -- Atlases; Neoplasms -- Classification; Medical; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Chirurgie; Tumors; Atlases; Electronic books; Electronic books